2019
DOI: 10.1183/16000617.0083-2019
|View full text |Cite
|
Sign up to set email alerts
|

Update on oral appliance therapy

Abstract: Oral appliances are increasingly recommended for selected patients with obstructive sleep apnoea (OSA) and those who do not tolerate nor prefer continuous positive airway pressure. The most commonly used oral appliance advances the lower jaw during sleep, the so-called mandibular advancement device (MAD). Patients seek treatment because of disturbing snoring, daytime symptoms, apnoeas that disturb sleep and the longer term consequences with regard to cardiovascular risks. MADs reduce the apnoea–hypopnoea index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 85 publications
1
29
0
1
Order By: Relevance
“…Other complications include face acne, mask leaks causing dry eyes, chest pain, bloating, infections from improper cleaning and not to mention the cost of maintaining the PAP device. For mild OSA, other treatment options include mandibular advancement device [9], positional therapy [10], and the novel eXciteOSA treatment. These also have better compliance than PAP machines.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications include face acne, mask leaks causing dry eyes, chest pain, bloating, infections from improper cleaning and not to mention the cost of maintaining the PAP device. For mild OSA, other treatment options include mandibular advancement device [9], positional therapy [10], and the novel eXciteOSA treatment. These also have better compliance than PAP machines.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Mandibular advancement devices are the most commonly used and evaluated appliances and increase upper airway diameter by advancing the mandible forward. 26 Most clinical commissioning groups do not provide guidance for treatment with mandibular advancement devices, with a minority funding their use in the presence of CPAP intolerance. National Institute for Health and Care Excellence guidance considers mandibular advancement devices as a potential treatment modality for moderate OSA, but uncertainty remains because of insufficient data for their effectiveness compared with CPAP in mild and severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…CPAP and MAD keep the upper airway open during sleep. It has been suggested that CPAP and MAD therapies attenuate some cardiovascular diseases including atherosclerosis, hypertension, heart failure, and cardiac arrhythmias ( Barnes et al, 2004 ; Gotsopoulos et al, 2004 ; Bradley and Floras, 2009 ; Marklund et al, 2019 ; Yamamoto et al, 2019 ; Chen et al, 2021 ; O’Donnell et al, 2021 ).…”
Section: Hypoxia and Cardiovascular Diseasesmentioning
confidence: 99%